Enhancing The 6Cs as 21st Century Skills Among Higher Education Students Through An Entrepreneurial Project Learning - Khotimah, Sofiatul; Bambang, Bambang; Purwati, Atiek Sri; Aysi, Siti Aenandari Hadatul (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
The purpose of this study is to examine the impact of enhancing 21st-century skills, specifically the 6Cs (critical thinking, collaboration, communication, creativity, citizenship, and character), through project-based entrepreneurship learning. The research utilized a quantitative approach by surveying with questionnaires on two different class groups. The sample in this study consists of undergraduate students from the Faculty of Economics and Business at Universitas Jenderal Soedirman, selected through a random sampling technique comprising 104 students. The data were analyzed using SPSS 27 software, including the stages of classical assumption testing and an Independent Sample T-Test. The results indicate that the implementation of project-based entrepreneurship learning has a significant impact on enhancing 6C skills among students. Statistical tests indicate a significant difference between the group participating in entrepreneurship PjBL and the group that did not, with the average 6C skills being higher in the PjBL group. The integration of project-based entrepreneurship learning into the higher education curriculum is recommended to further develop 6C skills among students.